Analisis Pengaruh Kepemimpinan Dan Komunikasi Terhadap Kinerja Manajemen Rumah Sakit - Candra Mizwar; Dety Mulyanti (Universitas Muhammadiyah Manado, 2023)
Based on the Regulation of the Minister of Health of the Republic of Indonesia No. 72 of 2016, a hospital is an individual health service facility that provides inpatient and outpatient care, therefore quality services that must be fulfilled by hospitals. One of the efforts to improve the quality of service to the community is to improve the performance of the hospital professionally and independently. This study uses a literature review study approach using several sources selected based on inclusion and exclusion criteria that have been set by researchers. that: 1) Leadership style affects management performance. 2) Communication affects Management performance.